Determinants of Readmission in Chronic Obstructive Pulmonary Disease (COPD) Patients at Meuraxa Regional Hospital Banda Aceh - Ami Maisura; Asniar; Marlina Marlina (Rifa'Institute, 2026)
Introduction: The high readmission rates in patients with chronic obstructive pulmonary disease (COPD) present a significant clinical and financial burden to the healthcare system. Identifying the dominant determinants is critical to maximizing targeted transitional nursing intervention strategies. Objective: This study aimed to analyze the determinants associated with readmission rates in COPD patients at Meuraxa Regional Hospital in Banda Aceh. Methods: This quantitative study employed a correlational approach with a cross-sectional design. The purposive sampling technique was used to select 121 respondents as the study sample. Data were gathered using medical records, the International Physical Activity Questionnaire (IPAQ), and the COPD Assessment Test (CAT) and thereafter analyzed using the chi-square test and logistic regression. Results and Discussion: The analysis revealed that diseases apart from COPD (p=0.016), history of exacerbations (p=0.001), COPD severity (p=0.026), smoking behaviors (p<0.001), history of ICU admission (p<0.001), and physical activity (p<0.001) were significantly associated with readmission rates. ICU admission history emerged as the predominant factor with the strongest association with readmission (OR=17.024). Conclusion: This finding confirms that absolute functional vulnerability after intensive care is the foremost predictor of readmission in COPD patients. Therefore, hospitals are recommended to implement a post-discharge multidisciplinary transitional management model to optimize education and social support, thereby disrupting the cycle of readmission